Squamoid eccrine ductal carcinoma - Maria Isabel Ramos Saraiva; Marcella Amaral Horta Barbosa Vieira; Larissa Karine Leite Portocarrero; Rafael Cavanellas Fraga; Priscila Kakizaki; Neusa Yuriko Sakai Valente (Sociedade Brasileira de Dermatologia, 2016)
Abstract Squamoid eccrine ductal carcinoma is an eccrine carcinoma subtype, and only twelve cases have been reported until now. It is a rare tumor and its histopathological diagnosis is difficult. Almost half of patients are misdiagnosed as squamous cell carcinoma by the incisional biopsy. We report the thirteenth case of squamoid eccrine ductal carcinoma. Female patient, 72 years old, in the last 6 months presenting erythematous, keratotic and ulcerated papules on the nose. The incisional biopsy diagnosed squamoid eccrine ductal carcinoma. After excision, histopathology revealed positive margins. A wideningmargins surgery and grafting were performed, which again resulted in positive margins. The patient was then referred for radiotherapy. After 25 sessions, the injury reappeared. After another surgery, although the intraoperative biopsy showed free surgical margins, the product of resection revealed persistent lesion. Distinction between squamoid eccrine ductal carcinoma and squamous cell carcinoma is important because of the more aggressive nature of the first, which requires wider margins surgery to avoid recurrence.